PERANAN KURSUS CALON PENGANTIN SEBELUM PERNIKAHAN DALAM MENGATASI PROBLEMATIKA RUMAH TANGGA (STUDI DI KANTOR URUSAN AGAMA KECAMATAN WOLO) - Muhammad Ardan; Muhammad Yusuf Nasir; Rahmat Mansur (Jurnal Syariah Hukum Islam, 2022)
The occurrence of a rift in the household is due to the lack of provision and knowledge about the real family. There are so many hopes for the continuity of a marriage but in the middle of the road it runs aground which leads to divorce due to the lack of readiness of both parties in navigating the household. In order for all individuals to have mental, physical and material readiness at the level of marriage and so that households have strong resistance preparation in facing problems from internal and external influences. Pre-marital guidance is one of the BP-4 programs that is considered important. The type of research used in this research is descriptive analysis. The approach used by the author in this research is a qualitative approach. The conclusion about the bride-to-be course in Wolo District can be concluded that, the role of the bride-to-be course is very important for welfare in building a sakinah mawaddah warrahmah household and avoiding divorce because it has provisions and knowledge about the rights and obligations of the household.